Male breast cancer - a single center experience - Đurišić Igor; Žegarac Milan; Kocić Milan; Jokić Vladimir; Vučić Nikola; Petrović Ognjen; Santrač Nada; Končar Jovana; Ivezić Anđela; Nikolić Srđan (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. Male breast cancer is an exceptionally rare disease, accounting for only 0.5% of all male cancer cases, with an incidence of less than one case per 100,000 men annually. This study aims to present the experience of the Institute for Oncology and Radiology of Serbia (IORS) in managing male breast cancer. Methods. This retrospective study included all male patients treated at IORS for breast cancer during the period from 1997 to 2016. In total, 124 cases were included in this study and analyzed regarding demographic, clinical, and pathohistological characteristics, therapeutic approach, and treatment outcomes. Results. Most patients were in stages IIa (27.4%) and IIIb (33.9%). Modified Madden radical mastectomy was performed on 70% of patients. The most prevalent pathohistological tumor type was ductal invasive carcinoma, most frequently in the T2 stage. Most patients (92.1%) had a positive estrogen receptor (ER) and progesterone receptor status (92.1% and 82.4%, respectively), while human epidermal growth factor receptor 2 status was negative in 60% of the patients. The median overall survival was 121 months. Positive ER status was identified as the most important predictor of overall survival, while patients with initial stage IIIa/IIIb/IV disease had a greater risk of disease progression. Conclusion. Our research indicates that patients with ER-positive tumors, who are diagnosed with the disease early and do not have any distant or local metastases have significantly better overall survival rates.